Hubungan Asupan Natrium, Gaya Hidup, dan Faktor Genetik dengan Tekanan Darah pada Penderita Penyakit Jantung Koroner - Bertalina Bertalina; Suryani AN (Politeknik Kesehatan Tanjung Karang, 2017)
One of degenerative disease that caused by heart function declining and blood vessels. The major risk factors for coronary heart disease is blood pressure. Blood pressure can be affected by various factors such as age, gender, hypertension genetic factors, dietary intake, and lifestyle. This research determines the effects of sodium intake, lifestyle and genetic factors on coronary heart disease (CHD) patient’s blood pressure. This research was analytic research with cross sectional approach. Independent variables in this research are sodium intake, physical activity, smoking habits, and hypertension genetic factors with dependent variable is blood pressure in CHD patients. 96 CHD patients were admitted in the research. Respondents characteristics were mostly men (56.3%), 46-55 years old (36.5%) and 56-65 years old (36.5%), most education backgrounds was high school (41.7%), and without any occupation (32.3%). Most respondents had high blood pressure (51%), inadequate sodium intake (52.1%), have moderate physical activity (92.7%), do not smoke (91.7%), and have hypertension genetic factor (57.3%). Based on bivariate results showed that there was a significant correlation between sodium intake (p-value=0.004) and hypertension genetic factors (p-value=0.001) with CHD patient’s blood pressure but there was no significant correlation in physical activity (p-value=1.000) and smoking habits (p-value=1.000). It is concluded that controlling food intake and maintain normal blood pressure could minimize heart failure and death risk in CHD patients.